First manic episode associated with use of human chorionic gonadotropin for obesity: a case report. (18th December 2013) - Sanches, Marsal; Pigott, Teresa; Swann, Alan C; Soares, Jair C
<x xml:space="preserve">Abstract</x> Background Although highly controversial, the treatment of obesity with exogenous human chorionic gonadotropin (HCG) remains popular in the USA. We report the case of a patient whose first manic episode was associated with the use of HCG for weight loss. Case report A 32‐year‐old female patient was admitted to our psychiatric inpatient unit due to a two‐week history of manic symptoms. She had no previous history of manic or hypomanic episodes and had completed a 45‐day course of sublingual HCG for weight loss immediately prior to the onset of the manic episode. The patient was treated with lithium carbonate and aripiprazole, and progressed with improvement in the symptoms. Conclusion While it is not possible to definitively link the HCG use to the development of mania, available evidence suggests that HCG may have a contributing role in triggering manic symptomatology.